Toxic Profile of Benznidazole in Patients with Chronic Chagas Disease: Risk Factors and Comparison of the Product from Two Different Manufacturers - Molina, I.; Salvador, F.; Sánchez-Montalvá, A.; Treviño, B.; Serre, N.; Sao Avilés, A.; Almirante, B. (Antimicrobial agents and chemotherapy, 2015)
Benznidazole is considered the first-line treatment option against Chagas disease. The major drawback of benznidazole is its toxicity profile. The main objectives of this study were to describe the adverse events (AEs) in patients with chronic Chagas disease treated with benznidazole, determine the risk factors involved and compare the toxic profiles of two different preparations of the drug from ELEA and Roche. A total of 746 patients were diagnosed with Chagas disease in a 5-year period, and of these 472 were treated with benznidazole. A high proportion of patients ( n = 360 [76%]) suffered AEs, the most frequent being those related to hypersensitivity (52.9% of patients), headache (12.5%), and epigastric pain (10.4%). In 72 (12.7%) cases, treatment was discontinued. Overall, women had a higher incidence of AEs compared to men (81.3% versus 66%, P = 0.001) and were subject to higher levels of hypersensitivity-related events. Dermatological events, digestive tract manifestations, and general symptoms had a greater likelihood to appear around day 10 and neurological AEs around day 40 after starting treatment. With respect to liver function and hematological tests, the majority of patients did not suffer significant perturbation of liver enzymes or altered blood cell counts. However, 14 patients suffered from neutropenia, and 14 patients had aminotransferase levels that were more than four times the upper limit of the normal range. Patients treated with the ELEA benznidazole product experienced more arthromyalgia, neutropenia, and neurological disorders (mainly paresthesias) than those treated with the Roche product. Both drug products resulted in approximately the same percentage of permanent withdrawals.